2009
DOI: 10.1016/j.expneurol.2008.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic degeneration and memory loss delayed by vitamin E in a Down syndrome mouse model

Abstract: Down syndrome (DS) individuals develop several neuropathological hallmarks seen in Alzheimer's disease, including cognitive decline and the early loss of cholinergic markers in the basal forebrain. These deficits are replicated in the Ts65Dn mouse, which contains a partial trisomy of murine chromosome 16, the orthologous genetic segment to human chromosome 21. Oxidative stress levels are elevated early in DS, and may contribute to the neurodegeneration seen in these individuals. We evaluated oxidative stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 81 publications
9
104
1
Order By: Relevance
“…In previous studies other authors have observed an increase of calbindin D-28k immunoreactive interneurons in 30 days old animals [43]; however, another study using 10 months old animals reflects a reduction in the density of this subpopulation of interneurons in the hippocampus [41,42]. Our animals are young adults (4-5 months old) and they present a higher density of calbindin D-28k neurons in the hippocampus than controls.…”
Section: Interneurons Expressing Calcium Binding Proteinssupporting
confidence: 37%
“…In previous studies other authors have observed an increase of calbindin D-28k immunoreactive interneurons in 30 days old animals [43]; however, another study using 10 months old animals reflects a reduction in the density of this subpopulation of interneurons in the hippocampus [41,42]. Our animals are young adults (4-5 months old) and they present a higher density of calbindin D-28k neurons in the hippocampus than controls.…”
Section: Interneurons Expressing Calcium Binding Proteinssupporting
confidence: 37%
“…Staining density, measured with a gray scale ranging from 0 to 256, was obtained when background staining was subtracted from mean staining intensities for each section. Mean intensity values were averaged per animal and then analyzed for statistical significance using GraphPad Prism version 6 (GraphPad Software, La Jolla, CA) as described previously [12,40,41].…”
Section: Densitometrymentioning
confidence: 99%
“…The evidence as to whether Ts65Dn mice have elevated levels of oxidative stress has been very limited. Now, oxidative stress has been demonstrated in the brains of Ts65Dn mice, and long-term treatment with vitamin E seems to reverse the elevated oxidative stress, to delay the memory loss, to preserve markers of cholinergic cell loss, and to preserve hippocampal morphology in these mice (Lockrow et al 2009). There is also some evidence that oxidative stress may be elevated in thymocytes and macrophages of Ts65Dn mice (Paz-Miguel et al 1999).…”
Section: Mouse Models and The Study Of Dsmentioning
confidence: 99%
“…A particularly intriguing set of recent results demonstrates that treatment of mouse models, notably Ts65Dn mice, with a variety of agents, appears to improve learning and memory and perhaps brain structure in these mice (Lockrow et al 2009;Costa et al 2008;Rueda et al 2008;Fernandez et al 2007). So far, these studies have been carried out on adult mice.…”
Section: Possible Therapies For Dsmentioning
confidence: 99%